Ecology of the brain: the phenomenology and biology of the embodied mind - Fuchs, Thomas (Oxford University Press, 2018)
Introduction -- Part 1. Criticism of neurobiological reductionism. Cosmos in the head? -- The brain as the subject's heir? -- Part 2. Body, person, and the brain. Foundations : subjectivity and life -- The brain as an organ of the living being -- The brain as an organ of the person -- The concept of dual aspectivity -- Implications for psychiatry and psychological medicine -- Conclusion
Hier auch später erschienene, unveränderte Nachdrucke
Originally published as "Das Gehirn - ein Beziehungsorgan" by W. Kohlhammer GmbH, 2007. - "This book is based on a German precursor entitled "Das Gehirn - ein Bezeihungsorgan" ..., which recently appeared in its fifth edition (Fuchs 2016), ... albeit in a completely revised and extended form." - Seite v
Literaturverzeichnis (Seite 293-324) und Index
Keywords: Anthropologie; Gehirn